Enhances Community Economic Welfare with Village Fund Allocation and Village Policies - Fitra Arlina Nst (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study describes the benefits of village fund allocation, the benefits of village funds and village policies on community welfare. This is also done to find out whether the benefits of village fund allocation, the benefits of village funds and village policies equally affect the welfare of the community. This research was conducted in the village of Uteun Pulo, East Seunagan district, Nagan Raya district. The respondents consisted of 38 heads of families from various educational backgrounds and different occupations. All data were processed by multiple regression analysis by looking at the validity, reliability, and hypothetical testing with F t test and determination test. The results of this study indicate that the benefits of village fund allocation